2020
DOI: 10.3390/cancers12082220
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Proton Pump Inhibitors Increase the Risk of Pancreatic Cancer? A Systematic Review and Meta-Analysis of Epidemiologic Studies

Abstract: Background: One of the most frequently used medications for treating gastrointestinal disorders is proton pump inhibitor (PPI), which reportedly has potential adverse effects. Although the relationship between the use of PPIs and the risk of pancreatic cancer has been extensively investigated, the results remain inconsistent. Hence, this meta-analysis aimed to evaluate such relationship. Methods: We searched for literature and subsequently included 10 studies (seven case–control and three cohort studies; 948,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Previous meta-analyses of observational studies on PPI uses and the risk of pancreatic cancer reported that there was a positive link between them [ 31 , 32 , 33 ], which is consistent with our findings. Laoveeravat et al [ 32 ] included seven studies with a total of 546,199 participants.…”
Section: Discussionsupporting
confidence: 93%
“…Previous meta-analyses of observational studies on PPI uses and the risk of pancreatic cancer reported that there was a positive link between them [ 31 , 32 , 33 ], which is consistent with our findings. Laoveeravat et al [ 32 ] included seven studies with a total of 546,199 participants.…”
Section: Discussionsupporting
confidence: 93%
“…In total, we identified 6241 articles, scrutinised 375 full‐text articles, and included 132 eligible articles (3.52%) for preliminary data extraction ( Figure S1). After the selection criteria for the overlapping meta‐analyses were applied, 61 articles were ultimately selected for evidence synthesis 6–8,31–88 . Agreement between reviewers for eligibility of articles was excellent (κ statistic = 0.8).…”
Section: Resultsmentioning
confidence: 99%
“…However, we identified some overlaps between PDAC-and PPI-associated species, resulting in a somewhat high false positive rate for PPI users (w20%). Given epidemiological evidence of positive associations of PPI use and the risk of PDAC, 54 the overlap of the microbial signatures (eg, increase in Streptococcus spp and Veillonella spp) implies that the gut microbiome altered by PPIs is responsible for the development or progression of PDAC.…”
Section: Discussionmentioning
confidence: 99%